Demonstration of preferential binding of SYBR Green I to specific DNA fragments in real-time multiplex PCR - Giglio, Steven (Oxford University Press, 2003)
SYBR Green I (SG) is widely used in real-time PCR applications as an intercalating dye and is included in many commercially available kits at undisclosed concentrations. Binding of SG to double-stranded DNA is non-specific and additional testing, such as DNA melting curve analysis, is required to confirm the generation of a specific amplicon. The use of melt curve analysis eliminates the necessity for agarose gel electrophoresis because the melting temperature (T(m)) of the specific amplicon is analogous to the detection of an electrophoretic band. When using SG for real-time PCR multiplex reactions, discrimination of amplicons should be possible, provided the T(m) values are sufficiently different. Real-time multiplex assays for Vibrio cholerae and Legionella pneumophila using commercially available kits and in-house SG mastermixes have highlighted variability in performance characteristics, in particular the detection of only a single product as assessed by T(m) analysis but multiple products as assessed by agarose gel electrophoresis. The detected T(m) corresponds to the amplicon with the higher G+C% and larger size, suggesting preferential binding of SG during PCR and resulting in the failure to detect multiple amplicons in multiplex reactions when the amount of SG present is limiting. This has implications for the design and routine application of diagnostic real-time PCR assays employing SG.